Study on generation and composition of solid waste produced in UNIMAS cafeterias - Zarak, S.A.M; Razali, I. (Universiti Malaysia Sarawak (UNIMAS), 2009)
UNIMAS's cafeterias generate solid waste everyday and there are 11 cafeterias operating in UNIMAS. The study involved two main cafeterias which are located at Bunga Raya and Alamanda colleges. The objective of the study was to determine the waste generation and composition of solid waste generated by the cafeterias. The study was done by collecting data from both cafeterias on Monday, Wednesday and Friday,